2003
DOI: 10.1889/1.1832437
|View full text |Cite
|
Sign up to set email alerts
|

25.2: Characterization of Physical Image Quality of 2‐ and 5‐Million‐Pixel Monochrome AMLCDs for Medical Imaging

Abstract: The physical image quality of two new high‐performance monochrome active matrix liquid crystal displays (AMLCDs), a 2‐ and a 5‐million‐pixel display, is reviewed. The performance is illustrated by examples (because of space limitations) of on‐axis and off‐axis characteristic curves, luminance range and contrast, luminance uniformity across the display screen, temporal modulation transfer function (MTF), spatial MTF, spatial noise power spectra and spatial signal‐to‐noise ratios. The LCDs are equipped with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In modern digital radiology operations, AMLCD monitors are increasingly being used in workstations due mostly to decreasing cost and smaller footprint. One key deficiency of AMLCDs is their non-Lambertian luminance emission [1]. In previous work, we have characterized the angular emissions of 3-, 5-, and 9-million-pixel AMLCDs [2,3] and found that large departures from the desired luminance response are present even for the highperformance medical AMLCDs included in our study.…”
Section: Introductionmentioning
confidence: 64%
“…In modern digital radiology operations, AMLCD monitors are increasingly being used in workstations due mostly to decreasing cost and smaller footprint. One key deficiency of AMLCDs is their non-Lambertian luminance emission [1]. In previous work, we have characterized the angular emissions of 3-, 5-, and 9-million-pixel AMLCDs [2,3] and found that large departures from the desired luminance response are present even for the highperformance medical AMLCDs included in our study.…”
Section: Introductionmentioning
confidence: 64%
“…The medical display with a high mega pixels is used to define the fine diagnosis and clinic to display with high density digital image such as X-ray, MRI and CT [1]. In recent, most hospital have to change from CRT to high resolution LCD display for diagnosis by using the digital image of medical information.…”
Section: Introductionmentioning
confidence: 99%